Tertiary Education and Economic Growth in Sub-Saharan Africa: The World Bank Report - Saint, William (International Higher Education, 2009)
Citing case studies in Africa and Asia, the World Bank's Report "Accelerating Catch-Up: Tertiary Education in Sub-Saharan Africa" argues that economic growth in these developing countries hinges on the human capitol fostered in secondary and tertiary education. Economic constraints and various structural and programmatic challenges threaten the ability for success in these institutions and creative solutions will be necessary to bolster growth.